Reinventing Urban Agriculture in Algerian Urban Policies: Stakeholders' Visions and Operational Strategy - Korchi, Meriem; Bendjaballah, Ouassila (Future Science, 2024)
Climate change and rapid urban growth are driving an increased demand for global resources, exacerbating environmental challenges. Addressing these issues necessitates the implementation of diverse strategies across various scales. Urban agriculture emerges as a potential solution to foster the resilience of urban entities. However, in the Mediterranean region, notably in Algeria, urban agriculture remains inadequately addressed in public policies, with agricultural plots in cities often earmarked as land reserves for future urban development. This study aimed to assess the perspective of urban actors in Annaba regarding urban agriculture and to identify and map agricultural activities within the city, with the goal of integrating them into urban policy frameworks. Interviews were conducted with decision-makers and farmers, complemented by spatial analysis. Findings revealed that although there is interest in urban agriculture, it is not effectively integrated into institutional and legal frameworks. Despite modest agricultural production primarily for self-consumption, urban agriculture projects hold potential for adoption in Algerian cities, offering a pathway towards enhancing urban sustainability.